(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2022)
Clay soil has been identified as a concern all around the world due to its swelling and shrinking qualities when it comes into touch with water. The load characteristics of soil are particularly low due to this clay feature. The influence of surkhi and ceramic tile dust on the geotechnical characteristics of clay soil is investigated in this study. The main goal of this research is to investigate the use of surkhi and ceramic tile dust as soil stabilisers in order to reduce the cost of soil stabilisation. The varied percentages of surkhi and ceramic tile dust, as well as their various combinations, were employed. . The soil at lower proportions of Optimum Water Content since there was a substantial improvement in Maximum Dry Density (MDD) (OMC). These materials not only give an alternative to the use of traditional materials, but they also aid in the reduction of pollution. Most of the time, these waste items are dumped in open areas, causing a lot of problems for the people who live in the region as well as the professionals who work there. Surkhi and ceramic tile dust may definitely be regarded an excellent stabilising element for clayey soil based on the findings.